A Mobile Phone App-Based Tai Chi Training in Parkinson's Disease: Protocol for a Randomized Controlled Study - Gao, Song; Kaudimba, Keneilwe Kenny; Cai, Jiaxin; Tong, Yao; Tian, Qianqian; Liu, Peize; Liu, Tiemin; Chen, Peijie; Wang, Ru (Frontiers in Neurology, 2021)
Introduction: With an increasing number of China’s aging population, Parkinson’s disease (PD) increases year by year. Persons with PD exhibit abnormal balance functions, leading to motor skills difficulties, such as unstable walking or even falling. Therefore, activities of daily living and quality of life are affected. This study aims to explore the effectiveness of Tai Chi training based on the mobile phone app in improving the balance ability of persons with PD. Methods and analysis: A randomized, single-blind, parallel controlled trial will be conducted in this study. One hundred and forty-four persons with Parkinson’s disease who meet the inclusion criteria will be randomly divided into a 1: 1: 1 ratio: (1) control group, (2) basic experimental group (basic app with no Tai Chi training features), (3) balanced-enhanced experimental group (basic app with Tai Chi training features). Individuals with Parkinson’s disease will be evaluated on balance and motor function outcomes. The primary outcome measure is the limits of stability (including the maximum excursion & direction control); the secondary outcome measures include the Unified Parkinson’s Disease Rating Scale Ⅲ (UPDRS-Ⅲ), Berg Balance Scale (BBS), Functional reach test (FRT), Timed Up & Go (TUG), 6-Minute Walk Test (6MWT), PDQ-39 scale. Each group of patients will go through an assessment at baseline, 17 weeks, and 33 weeks. Discussion: This study will evaluate the effectiveness of the mobile phone app Tai Chi training on the balance function of persons with PD. We assume that a challenging Tai Chi project based on a mobile phone app will improve balance in the short and long term. As walking stability progresses, it is expected that daily activities and quality of life improves. These findings will be used to improve the effectiveness of future home management measures for persons with PD. Ethics and dissemination This study has been approved by the ethical review committee of the Shanghai University of Sport (Approval number: 102772019RT056). Informed consent will be obtained from all participants or their guardians. The authors intend to submit the study findings to peer-reviewed journals or academic conferences to be published. Trial registration number: Chinese Clinical Trial Registry (ChiCTR2000029135).